Age 13 Language and Reading Outcomes in Late-Talking Toddlers. - Rescorla, Leslie (Journal of Speech, Language & Hearing Research, 2005)
Language and reading outcomes at 13 years of age were examined in 28 children identified at 24 to 31 months as late talkers, all of whom came from middle- to upper-class socioeconomic status (SES) families and had normal nonverbal ability and age-adequate receptive language at intake. Late talkers were compared with a group of 25 typically developing children matched at intake on age, SES, and nonverbal ability. As a group, late talkers performed in the average range on all standardized language and reading tasks at age 13. However, they scored significantly lower than SES-matched peers on aggregate measures of vocabulary, grammar, and verbal memory, as well as on reading comprehension. They were similar to comparison peers in reading mechanics and writing aggregates. Intercorrelations between outcome measures were moderately high, suggesting considerable shared variance. Regression analyses indicated that age 2 Language Development Survey vocabulary score was a significant predictor of age 13 vocabulary, grammar, verbal memory, and reading comprehension. Findings suggest that slow language development at age 2-21/2 is associated with a weakness in language-related skills into adolescence relative to typically developing peers. Reprinted by permission of the publisher.